Mosquito Vector Biting and Community Protection in a Malarious Area, Siahoo District, Hormozgan, Iran - KH Shahandeh; HR Basseri; A Pakari; A Riazi (Tehran University of Medical Sciences, 2010)
Background: Use of bed-net continues to offer potential strategy for malaria prevention in endemic areas. Local communities are indispensable during design and implementation stages. Methods: A cross-sectional study of 192 randomly selected inhabitants was carried out in malarious zone, Siahoo direstrict, Hormozgan Province, southern Iran. In addition, we monitored human landing periodicity of main malaria vectors and as well as self-protection of inhabitant in the study area for a period of one transmission season between April to October 2006. Results: The biting activities were seen throughout the whole night for three malaria vectors, Anopheles fluviatilis, An. stephensi and An. Dthali, and  An. fluviatilis exhibiting bimodal peaks, the first at midnight (0:00-1:00) and the other before dawn (5:00−6:00 am) but the maximum biting activity of An. stephensi was occurred at second quarter of night (11:00-12:00 pm). The majority of interviewers (83.3%) knew that malaria was transmitted by mosquitoes and 70.3% of them stated that bed-net is the best control measures. Most subjects (62%) did not have a mosquito net. Conclusion: Study subjects were aware of an association between mosquito bite and malaria transmission. Health workers at different levels of the health care delivery system should disseminate relevant information about self-protection to help community members to be involved more in malaria control.